Pendidikan Politik bagi Generasi Zelenial dan Pemilih Pemula pada Pemilihan Umum Tahun 2024 - Bayu Aji, Alan (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
The majority of voters in the 2024 election are the young generation who are classified as the millennial generation and the millennial generation, the majority of whom are first-time voters. Based on this, it became the background for carrying out Political Education activities for the Zelenial Generation and New Voters in the 2024 General Election. This activity was carried out on February 7 2024 by presenting student participants from several universities in the Banyumas Regency area. The service activity method is carried out directly and packaged in the form of a public discussion. The result of this activity is that the younger generation still has minimal knowledge regarding the essence of general elections. Based on this, this service provides 3 main things about general elections, first, Understanding of Substantial Democracy, second, History of the Implementation of General Elections in Indonesia, and third, the Role of the Young Generation in the 2024 General Election. These three main materials are expected to be sufficient provision for the young generation. in participating in the 2024 elections.